Utilization of fly ash and bottom ash waste: a study at PLTU Tanjung Jati B, Jepara, Indonesia - Prayoga, M. Bayu Rizky; Afla, Rohadatul Aisy (Asian Journal of Toxicology, Environmental, and Occupational Health, 2023)
The high energy needs force the massive use of coal. PLTU as one of the largest energy-producing industries currently has a significant impact on the environment and social economy. One of the wastes from PLTU activities is fly ash and bottom ash (FABA). By taking a research study at the Tanjung Jati B PLTU one of the largest PLTUs in Indonesia, the authors try to see the impact of FABA waste on the environment and analyze the potential that can be utilized. The research approach used is quantitative by collecting data through literature studies. The results showed that FABA had a negative impact on the environment, especially when it was only left buried in landfills. On the other hand, FABA has the potential to improve the economy, especially for the people around the PLTU industry, including in the agricultural aspect. One of the benefits of FABA is for building construction purposes with a mixture of 20% to 35%. For agriculture, FABA is proven for soil enrichment on a small scale with a mixture of 35% to 50% and can increase the nutrients in the soil .